2021
DOI: 10.3389/fcimb.2021.706849
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cold Water-Immersion Restraint Stress Induces Intestinal Injury and Reduces the Diversity of Gut Microbiota in Mice

Abstract: Growing evidence has demonstrated that stress triggers gastrointestinal (GI) disorders. This study aimed to investigate how the acute cold water-immersion restraint (CWIR) stress affects intestinal injury and gut microbiota (GM) distribution. Male C57BL/6 mice were used to establish a CWIR animal model. Hematoxylin–eosin and periodic acid–Schiff staining were performed to assess intestinal histopathological changes. Reverse transcription quantitative polymerase chain reaction (RT-qPCR) analysis and immunofluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Exposure to cold environments can reduce the abundance of the intestinal flora. The abundance of intestinal flora decreased after being soaked in cold water for 1 h ( Zhang et al, 2021 ). Furthermore, Zietak et al (2016) housed mice in a cold environment and observed a decrease in the abundance of their intestinal flora.…”
Section: Factors Affecting the Intestinal Flora In The Qinghai–tibet ...mentioning
confidence: 99%
“…Exposure to cold environments can reduce the abundance of the intestinal flora. The abundance of intestinal flora decreased after being soaked in cold water for 1 h ( Zhang et al, 2021 ). Furthermore, Zietak et al (2016) housed mice in a cold environment and observed a decrease in the abundance of their intestinal flora.…”
Section: Factors Affecting the Intestinal Flora In The Qinghai–tibet ...mentioning
confidence: 99%
“…Although the pathophysiology of IBS remains unclear, one major cause has been attributed to psychosocial stress from various sources. Studies showed that acute cold WIRS could cause IBS‐like disorders, increase the permeability of intestinal mucosa, and cause severe intestinal inflammation and injury 49 . Six or seven hours daily WIRS could induce gastric ulcers, 50,51 however, Yasugaki et al confirmed that the use of a milder regimen did not lead to gastric ulcers, 40 and this approach could lead to anxiety‐depression‐like phenotypes and gastrointestinal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…All animals were housed in a 12 h day-night cycle with free access to water and food at 22 ± 1°C and 60 ± 10% humidity. The mice in corresponding groups were administrated with acute CWIR for 1 h using the same protocol described in our previous study (13). Briefly, mice were restrained in polyvinyl chloride tubes and vertically immersed in cold water with a temperature around 10°C, at the level of sternum xiphoid.…”
Section: Animal Administrationmentioning
confidence: 99%
“…Although acute stress frequently causes gastrointestinal (GI) dysfunction, few studies have reported CWIR-induced intestinal damage and manifestations. We previously uncovered that acute CWIR resulted in damaged intestinal mucosa and decreased gut microbiota diversity (13), implying that stress-induced intestinal disorders exist.…”
Section: Introductionmentioning
confidence: 99%